2021
DOI: 10.1212/nxi.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament Light in CSF and Plasma Is a Marker of Neuronal Damage in HTLV-1–Associated Myelopathy and Correlates With Neuroinflammation

Abstract: Background and ObjectivesTo evaluate the usefulness of CSF and plasma neurofilament light (Nf-L) as a biomarker for human T-cell lymphotropic virus type 1 (HTLV-1)-associated myelopathy (HAM).MethodsNf-L, CXCL10, and neopterin were measured by ELISA in 83 CSF samples obtained from 49 individuals living with HTLV-1/2. Plasma Nf-L was also measured by single molecule array. Results were correlated with duration of disease, age, mobility, CSF cell counts, CSF protein, and HTLV-1 proviral load.ResultsNf-L was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Notably, the high TNF/GlycA group also comprised the only fatal case among 43 HAM/TSP patients, with death related to HAM/TSP as described in our previous study [7]. Several other non-cytokine biomarkers, such as CXCL10 (also known as IP-10), Neurofilament Light Chain (NFL), and Chitotriosidase-1 (encoded by the CHIT1 gene) have recently been proposed as biomarkers for HAM/TSP disease progression [4,5,8,33,[53][54][55][56][57][58]. Although most inflammatory biomarkers correlate reasonably well between plasma and CSF [53][54][55][56][57][58][59], most of these published studies have focused on CSF samples for the quantification of these biomarkers, which was neither logistically nor ethically possible in our cohort.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Notably, the high TNF/GlycA group also comprised the only fatal case among 43 HAM/TSP patients, with death related to HAM/TSP as described in our previous study [7]. Several other non-cytokine biomarkers, such as CXCL10 (also known as IP-10), Neurofilament Light Chain (NFL), and Chitotriosidase-1 (encoded by the CHIT1 gene) have recently been proposed as biomarkers for HAM/TSP disease progression [4,5,8,33,[53][54][55][56][57][58]. Although most inflammatory biomarkers correlate reasonably well between plasma and CSF [53][54][55][56][57][58][59], most of these published studies have focused on CSF samples for the quantification of these biomarkers, which was neither logistically nor ethically possible in our cohort.…”
Section: Discussionmentioning
confidence: 64%
“…Several other non-cytokine biomarkers, such as CXCL10 (also known as IP-10), Neurofilament Light Chain (NFL), and Chitotriosidase-1 (encoded by the CHIT1 gene) have recently been proposed as biomarkers for HAM/TSP disease progression [4,5,8,33,[53][54][55][56][57][58]. Although most inflammatory biomarkers correlate reasonably well between plasma and CSF [53][54][55][56][57][58][59], most of these published studies have focused on CSF samples for the quantification of these biomarkers, which was neither logistically nor ethically possible in our cohort. Moreover, our goal was to define biomarkers that can be easily implemented in clinical practice, such as non-invasive plasma/serum samples, which also allow repeated testing before and after treatment at regular intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofilament light chain (NEFL, also named NF-L) is a subunit of neurofilaments. A previous study reported that NEFL is a marker for neuronal damage and is associated with neuroinflammation (Rosadas et al, 2021). CSF NF-L expression was significantly increased in amyotrophic lateral sclerosis (ALS) and is of diagnostic and prognostic value for ALS (Rossi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies employing blood samples used the presence of inflammatory markers such as C-reactive protein (CRP, a widely-studied cytokine which represents acute inflammation) and cytoskeletal NFL (released into CSF and blood as the result of neuroaxonal impairment) in the diagnosis of neurological diseases [ 20 ]. These studies suggested that NFL levels in both CSF and plasma correlate with levels of well-known markers of neuroinflammation such as C-X-C motif chemokine ligand 10 (CXCL10), neopterin [ 21 ], the kynurenine-to-tryptophan ratio, and kynurenine metabolites, which are important mediators in neuroinflammation [ 22 ]. Thus, these researchers concluded that blood serum NFL may be used as an indirect biomarker of neuroinflammation.…”
Section: Important Genes Involved In the Development Of Hiv-associate...mentioning
confidence: 99%